Lacrimal Gland Repair after Short-term Obstruction of Excretory Duct in Rabbits - Hui Lin (Nature Portfolio, 2017)
Abstract Aqueous tear-deficient dry eye is a multifactorial chronic disorder in which the lacrimal glands fail to produce enough tears to maintain a healthy ocular surface. The existence of lacrimal gland stem/progenitor cells was proposed in several species, yet their origin and characteristics are not very clear. Here, we investigated the presence of resident progenitor cells and their regenerative potential in a rabbit model with lacrimal gland main excretory duct ligation-induced injury. The ligation-injured lacrimal glands temporarily decreased in weight and had impaired tear secretion. Protein expression profiles and transcriptional profiles were obtained from injured tissue. Isolated lacrimal gland progenitor cells were tested and characterized by stem cell-related marker evaluation, single cell clonal assay and three-dimensional (3-D) culture. The results of our study indicate that lacrimal glands are capable of tissue repair after duct ligation-induced injury, likely involving resident stem/progenitor cells and epithelial-mesenchymal transitions. Lacrimal gland progenitor cells isolated from ligated tissue can differentiate in 3-D culture. The results provide further insights into lacrimal gland stem/progenitor cell physiology and their potential for treating severe cases of tear deficiency.